Resilience in Higher Education: A Complex Perspective to Lecturers' Adaptive Processes in Response to the COVID-19 Pandemic - Fabio Bento; Andréa Giglio Bottino; Felipe Cerchiareto Pereira; Janimayri Forastieri de Almeida; Fabiana Gomes Rodrigues (MDPI AG, 2021)
The present article discusses the dynamics of system resilience, focusing on the case of a university college in Brazil. It investigates the experience of lecturers of this educational institution in the initial months of the COVID-19 pandemic. This is exploratory basic qualitative research, aiming at understanding how the university college self-organized in this period. This research focused on local adaptation processes and was conducted through interviews with a sample of lecturers from the study programs offered by the university college. A text analysis software was used to analyze the data generated according to the three aspects of social-ecological resilience. The analytical framework of this research applies the concept of resilience in a socio-ecological system to discuss emergent organizational changes and learning in higher education. Systems resilience highlights adaptation processes characterized by an interplay of previous experience and emerging new knowledge. The findings describe the emergence of new practices and learning as faculty members encountered challenges brought on by the pandemic. Beyond learning new technological tools, the pandemic raised awareness of students' socio-economic backgrounds in the context of inequality in Brazil. However, resilience requires open communication among staff and across organizational levels about adaptation processes that have taken place during the pandemic.